Designing an Electronic Marketing Model Based on Social Networks –Case Study on Sports Equipment Manufacturing Companies - Ziba Mohammad Rezaee; Korosh Veisi; Adel Fatemi; Samira Aliabadi; Mohsen Smaeili (Sports Business Journal)
Purpose: Today, due to the potential of networks and social media, marketing has experienced significant growth in them. However, the mechanism by which a sports equipment manufacturing company can engage in this field is uncertain. Therefore, this study aimed to present an electronic marketing model based on social networks in sports equipment manufacturing companies.Methodology: This research was conducted qualitatively using a structural-functional analysis approach at the strategic level. The participants consisted of experts in sports marketing, media, and sports equipment production, and a snowball sampling method based on theoretical saturation was used to select 18 of them. The data collection tool was a semi-structured interview, and its validity, transferability, reliability, and conformability were examined. The data was analyzed using the coding method.Findings: We showed the company's marketing model production of sports equipment in the network social functions subject to five main aspects (opportunity, targeting, setting up, monitoring and optimization, and threats), and there are 19 major categories. This result showed electronic marketing based on social networks in the company production of sports equipment is a systemic process. Based on this, it is suggested that the company producing sports equipment is made for optimal use of the opportunity. The existing part of their marketing actions is the fluency of the media in social activities while keeping pace with statistics and content steps that are based on the opinion of experts, monitoring the threats in this area, and as much as possible based on the reasons for the political conditions of the country from the all-round presence on the platform foreigners should be avoided and if possible, in the network internal social activities to operated.Originality: This study helps to understand how companies producing sports equipment can effectively use social networks for marketing purposes.